PERANAN WANITA TANI DALAM PENERAPAN TEKNOLOGI BUDIDAYA SAYURAN DI LABAN PASIR PANT AI KECAMATAN SANDEN KABUPATEN BANTUL - Siska Ernitawati; Roso Witjaksono; Harsoyo Harsoyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
This research aimed to know the role of women farmers in the application of vegetables cultivation technology and the factors that affect the role of women farmers in the application of vegetables cultivation technology, andalso determine the influence of the role of women farmers and other factors that influence the adoption ofvegetables cultivation technology. Descriptive method with survey techniques is used in this research. Sampling villages andfarmer groups conducted purposively, while sampling of women farmers were chosen by simple random sampling. Total sample amounted to 60 women farmers consist of 30 women farmers from the Manunggal farmer groups and30 women farmers from the Pasir Makmur farmer groups. The proportion test and multiple linear regression test is the method analysis which is used. The results showed that the role of women farmers in the application ofvegetablescultivation technology in the middle category, while the rate of adoption of vegetables cultivation technology is high. The age and knowledge gave positive influence on the role of women farmers, while education, womenfarmers activityin extension, attitude, motivation, family members, total of productive family members, family income, and the cultural value orientation did not significantly affect on the role of women farmers. The age, education, and women farmersactivity in extension gave positive influence on the adoption of vegetables cultivation technology, while the role of women farmers, knowledge, attitude, motivation, family members, total of productive family members, family income, and the cultural value orientation did not significantly affect the adoption of vegetables cultivation technology